Pengembangan Pendidikan Agama Islam dalam Upaya Meningkatkan Kualitas Kepribadian Peserta Didik di SMAN 1 Karangbinangun Lamongan - Rokim Rokim (Akademika, 2020)
This research is motivated by the reality showing the influence of the development of Islamic education on the personality of students. The position of Islamic religious education as a compulsory subject in schools expected to contribute sufficiently in improving the morale or behavior of learners seems difficult to realize. Therefore it is necessary to hold the development of Islamic religious education as an alternative to overcome the problems of Islamic religious education. The purpose of this study is to determine the development of Islamic religious education in an effort to improve the quality of student personality, supporting and inhibiting factors of the development of Islamic religious education, and to overcome the factors inhibiting the development of Islamic religious education. This is a descriptive qualitative research. The subjects in this research are principal, PAI teachers and students of SMAN 1 Karangbinangun. While data collection techniques are through interview, observation and documentation. This study concluded that firstly, the development of Islamic religious education in an effort to improve the quality of personality is a conscious effort. Second, the supporting factors of the development of Islamic religious education are the expected results, materials and time allocations, methods, students, interaction between parents, good education environment, religious teachers in supporting student success and inhibiting factors are  less effective learning, educational curriculum, monotonous methods, less good environment, inadequate infrastructures. Third, to overcome the factors inhibiting the development of Islamic religious education is the approach must be effective, maximizing the competence of teachers, methods, creating a good environment, and providing school infrastructures to support  effective learning process.